2018
DOI: 10.1038/s41598-018-19387-x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Perfusion Insufficiency and Relationships with Cognitive Deficits in Alzheimer’s Disease: A Multiparametric Neuroimaging Study

Abstract: Micro- or macro-circulatory insufficiency has a negative impact in patients with Alzheimer’s disease (AD). This study used arterial spin-labeled magnetic resonance imaging (ASL-MRI) and ethylcysteinate dimer single-photon emission computed tomography (ECD-SPECT) in 50 patients with AD and 30 age-matched controls to investigate how hypoperfusion patterns were associated with gray matter atrophy and clinical data. All participants completed 3DT1-MRI, ECD-SPECT and ASL-MRI examinations. Medial temporal cortex (MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 68 publications
4
50
0
1
Order By: Relevance
“…In our findings, the estimated relative CBF at superior parietal lobule was significantly lower in more impaired MCI patients based on MMSE (< 28) compared to the cognitively normal group. This result was in agreement with prior studies that have reported decreased relative CBF in MCI or Alzheimer's pathology Huang et al, 2018). Interestingly, MCI patients with higher MMSE (³ 28) had higher estimated perfusion, albeit not statistically significant.…”
Section: Cbf Comparisons Between Controls and MCIsupporting
confidence: 92%
See 1 more Smart Citation
“…In our findings, the estimated relative CBF at superior parietal lobule was significantly lower in more impaired MCI patients based on MMSE (< 28) compared to the cognitively normal group. This result was in agreement with prior studies that have reported decreased relative CBF in MCI or Alzheimer's pathology Huang et al, 2018). Interestingly, MCI patients with higher MMSE (³ 28) had higher estimated perfusion, albeit not statistically significant.…”
Section: Cbf Comparisons Between Controls and MCIsupporting
confidence: 92%
“…This approach will be useful especially for studies that have large sample size (Habes et al, 2016), where reacquiring missing imaging modalities from the same subject is not practical. CBF estimation was better at the posterior regions, where many previous studies (Alsop et al, 2008;Dolui et al, 2017;Huang et al, 2018) and our results showed altered CBF in MCI or Alzheimer's pathology, suggesting the potential use of proposed method in those populations.…”
Section: Discussionsupporting
confidence: 64%
“…All failures of major organs lead to different degrees of cognitive impairment. Heart failure constitutes the most prevalent . Kidney failure represents another common example, the cognitive status often fluctuating with the dates of dialysis.…”
Section: Challengesmentioning
confidence: 99%
“…Heart failure constitutes the most prevalent. [15][16][17][18][19] Kidney failure represents another common example, the cognitive status often fluctuating with the dates of dialysis.…”
Section: Organ Failure and Brain Failurementioning
confidence: 99%
“…Segundo Huang et al (2018) Uma das limitações do estudo é a determinação do intervalo de tempo para as imagens de PET 11 C-pPIB (0 a 10 minutos), que foi inicialmente considerada para representar o padrão de distribuição do fluxo sanguíneo cerebral desse traçador em particular. Estudos recentes (Ponto, et al, 2019, Bilgel et al, 2019; mostraram que a melhor correlação de 11 C-pPIB e FSCr foi observada nas primeiras imagens (em tempos mais curtos de aquisição), segundo Peretti et al, (2019), a melhor correlação de 11 C-pPIB e FSCr é no intervalo de tempo preferido de 20 a 130 segundos de aquisição.…”
Section: Análise Visual E Individualunclassified